A Coordinated, Risk-Based, National Forest Biosecurity Surveillance Program for Australian Forests - Carnegie, Angus J.; Tovar, Francisco; Collins, Susie; Lawson, Simon A.; Nahrung, Helen F. (Frontiers in Forests and Global Change, 2022)
Australia has a comprehensive plant biosecurity system, with the federal government responsible for pre-border (e.g., off-shore compliance) and border (e.g. import inspections) activities, while state governments undertake a variety of post-border activities (e.g., post-border surveillance, management of pest incursions, and regulation of pests) designed to reduce exotic pest arrival and establishment. Once an exotic pest has established and spread, its management, like that of endemic species, becomes the responsibility of the land manager. There has been a growing understanding among plant industries of the need to be more engaged in post-border biosecurity activities, including resourcing and undertaking early-detection surveillance and contingency planning. Here we summarise Australia’s broader plant biosecurity system along with current, forest-specific biosecurity surveillance activities. We then introduce a proposal for a forest biosecurity partnership between the federal government, state governments and the forest sector to introduce a post-border, risk-based National Forest Pest Surveillance Program. We describe why there is a need for the Program, how it would improve biosecurity outcomes in relation to forests, its component activities, and identify the key stakeholders and beneficiaries.